Development of a culture-independent whole-genome sequencing of Nipah virus using the MinION Oxford Nanopore platform - Md. Mahfuzur Rahman; Mojnu Miah; Mohammad Enayet Hossain; Samiur Rahim; Sharmin Sultana; Syed Moinuddin Satter; Ariful Islam; Shannon L. M. Whitmer; Jonathan H. Epstein; Christina F. Spiropoulou; John D. Klena; Tahmina Shirin; et al. (Microbiology Spectrum)
ABSTRACT Nipah virus (NiV) is a deadly zoonotic pathogen in Southeast Asia causing severe respiratory and encephalitis symptoms with a high fatality rate. Whole-genome sequencing (WGS) is crucial for tracking transmission, conducting epidemiological analyses, and understanding NiV’s adaptive evolution. WGS is essential for analyzing genomes, particularly in understanding pathogen nature, and pathogenesis and aiding in the development of therapeutics. However, sequencing this highly contagious virus directly from samples is challenging in low- and middle-income countries lacking BSL-4 facilities. This study developed and optimized a culture-independent, high-throughput multiplex PCR-based third-generation sequencing protocol for NiV using the Oxford Nanopore Technology platform and a proposed bioinformatics pipeline to generate consensus genome sequences directly from environmental and clinical specimens. We amplified 12 NiV RT-PCR-positive specimens (11 clinical, one environmental) to produce 60 amplicons, each approximately 400 bp, covering the entire ~18.2 kb genome. Using a two-step reverse transcriptase PCR approach, libraries were prepared with a ligation sequencing kit. Raw sequence data were then analyzed using bioinformatics tools. A minimum of 10,000 total reads per sample provided a nearly complete coverage (>95%) of the NiV genome, even with low virus concentrations (Ct ≤ 32), with an average quality score of 10.2. The WGS of 12 NiV-positive samples achieved coverage between 95.71% (Ct 29.54) and 99.3% (Ct 22.34). The entire process, from RNA extraction to finished sequences, took only 24 h. We developed a portable, culture-independent, high-throughput sequencing workflow suitable for resource-limited settings, aiding in real-time monitoring, outbreak investigation, and detection of new NiV strains and genetic evolution.IMPORTANCEThe development of a culture-independent, high-throughput whole-genome sequencing (WGS) protocol for Nipah virus (NiV) using the Oxford Nanopore MinION technology marks a significant advancement in outbreak response, surveillance, and genomic analysis of NiV. NiV is an RG4 category C pathogen; working with the NiV virus is a deep concern of biosafety and biosecurity. It demands the development of biologically safe procedures to get genetic information. This protocol utilizes biologically safe samples that were collected into recommended lysis solution, multiplex PCR, and third-generation sequencing, effectively addressing challenges in sequencing NiV. This optimized workflow achieved over 95% genome coverage without the need for virus culture. It is a cost-effective, rapid, and efficient approach to the WGS of NiV, making it suitable for resource-limited settings like Bangladesh. The method enhances the capacity for outbreak investigations, epidemiological analyses, and monitoring virus, aiding in detecting emerging strains. This work contributes significantly to global pandemic preparedness and response efforts.